Comments on and illustrations of the WFUMB CEUS liver guidelines: Rare malignant mesenchymal liver lesions - Zadeh, Ehsan Safai; Schreiber, Nicole; Görg, Christian; Huber, Katharina Paulina; Möller, Kathleen; Berzigotti, Analisa; Thomsen, Thomas; Jenssen, Christian; Jung, Ernst-Michael; Lim, Adrian; Kitano, Masayuki; Shimizu, Ryo; et al. (Medical ultrasonography, 2024)
The diagnosis or rare mesenchymal malignant lesions of the liver may be a challenge owing to the rarity of the disease and is usually made by histological confirmation. An ultrasound examination with, if required, color Doppler sonography and contrast-enhanced ultrasound, taking into account the clinical background of the patient, may help to focus the differential diagnosis. In this review, we describe the pathological and ultrasound features of several rare mesenchymal malignant liver lesions which include undifferentiated sarcoma of the liver, leiomyosarcoma, angiosarcoma, fibrosarcoma, liposarcoma, and epithelioid hemangioendothelioma.